Review paper: General overview of control problems in wind power plants - Quang, Nguyen Phung (Journal of Computer Science and Cybernetics, 2014)
Wind power plants can be realized with different generator types using different control principles. The choice of the generator regardless of the control method, potentially destabilizes the grid, and can even lead to grid collapse. For independent grid (e.g. on islands) this risk is especially great. The report aimed at giving the reader a general overview of the control methods, and the developers a better  understanding of each generator type to get the right choice for their wind power project.